Upaya Penumbuhan Empati pada Guru IPS dalam Meningkatkan Sikap Peduli Sosial Siswa Kelas VII di MTs Binaya Ilmi Wongsorejo Banyuwangi - Alvi Wardatun Ni’mah; Jani Jani (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
The attitude of social care is important for every student to have with the existence of students' concern for their environment will make students a good person. Social care attitude is a person's attitude to help each other and help others who are in trouble. This study aims to (1) Describe the Efforts to Cultivate Empathy in Social Studies Teachers in Improving the Social Care Attitudes of Class VII Students at MTs Binaya Ilmi Wongsorejo Banyuwangi Academic Year 2023/2024, (2) Describe the Supporting and Inhibiting Factors of Social Studies Teachers in Improving Social Care Attitudes of Class VII Students at MTs Binaya Ilmi Wongsorejo Banyuwangi Academic Year 2023/2024 (3) Describe the Impact of Efforts to Cultivate Empathy in Social Studies Teachers in Improving Social Care Attitudes of Class VII Students at MTs Binaya Ilmi Wongsorejo Banyuwangi Academic Year 2023/2024. This research uses a qualitative approach with a case study research type. Data collection techniques in this study include observation, interviews, and documentation. The data analysis technique uses an inductive method which is divided into 4 steps: (1) Data Collection, (2) Data Condensation, (3) Data Presentation, (4) Conclusion. From the results of the study found that (1) Efforts to cultivate empathy in social studies teachers in improving the social care attitude of seventh grade students by providing exemplary, habituation and socialization. (2) Supporting factors in improving the social care attitude of students with the existence of socialization activities during morning apples, community service, fundraising and charity activities. While the inhibiting factors are students playing excessive gadgets, the existence of customs that have thickened in students and social change. (3) The impact of empathy cultivation efforts on social studies teachers in improving the social care attitude of seventh grade students is that students become enthusiastic when the teacher tells them to wipe the blackboard, students are able to be kind to other students and students have a good helping attitude.